2003
DOI: 10.1023/b:neur.0000020623.62043.33
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent elimination of neuromuscular synapses

Abstract: At developing neuromuscular synapses in vertebrates, different motor axon inputs to muscle fibers compete for maintenance of their synapses. Competition results in progressive changes in synaptic structure and strength that lead to the weakening and loss of some inputs, a process that has been called synapse elimination. At the same time, a single input is strengthened and maintained throughout adult life, consistently recruiting muscle fibers to contract even at rapid firing rates. Work over the last decade h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 106 publications
2
56
0
1
Order By: Relevance
“…Extensive experimental data support the view that the more active terminal or "cartel" gets stabilized, whereas less active ones withdraw, resulting in canonical elimination of polyneuronal innervation (8,11). It is generally believed that this synaptic competition is mediated by a "punishment" or "elimination" signal, produced by the postsynaptic cell, that causes the retraction of the inactive terminals, as well as a "protective" or "reward" signal that stabilizes the active terminal (10)(11)(12). Despite significant efforts over decades, the identity of the punishment or reward signals remains unknown (4,13).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Extensive experimental data support the view that the more active terminal or "cartel" gets stabilized, whereas less active ones withdraw, resulting in canonical elimination of polyneuronal innervation (8,11). It is generally believed that this synaptic competition is mediated by a "punishment" or "elimination" signal, produced by the postsynaptic cell, that causes the retraction of the inactive terminals, as well as a "protective" or "reward" signal that stabilizes the active terminal (10)(11)(12). Despite significant efforts over decades, the identity of the punishment or reward signals remains unknown (4,13).…”
mentioning
confidence: 93%
“…Activitydependent synaptic competition, a general process seen in many parts of the developing nervous system, plays a critical role in shaping patterns of neuronal connections (2)(3)(4)(5)(6)(7). At the neuromuscular junction (NMJ), for example, multiple axons compete for the same postsynaptic muscle cell during early postnatal life until all but one is eliminated (8)(9)(10). Extensive experimental data support the view that the more active terminal or "cartel" gets stabilized, whereas less active ones withdraw, resulting in canonical elimination of polyneuronal innervation (8,11).…”
mentioning
confidence: 99%
“…However, stable polyneuronal innervation of mature neuromuscular junctions is well-supported in amphibia, where two (or sometimes more) axons form synaptic connections that are distributed along the long axis of a single muscle fiber (Lateva et al, 2002). More recently, multiple endplates, subserved by different motoneurons (Duxson and Sheard, 1995;Happak et al, 1997;Zenker et al, 1990) and separated by up to 46 mm, have been identified on mature muscles in a variety of species (Wyatt and Balice-Gordon, 2003).…”
Section: Possible Implications Of Long-term Depression For Competitiomentioning
confidence: 99%
“…This can be seen during development and re-innervation of muscle when individual fibers receive transient innervation from two or more motoneurons (Wyatt and Balice-Gordon, 2003). Differences emerge in the strength of convergent inputs during the subsequent loss of the polyneuronal innervation of the muscle cell, and a role for activity-dependent retrograde modulation of synaptic strength in this process has been postulated (Colman et al, 1997;Kopp et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The suprathreshold excitation may produce global influence in the maturation of muscle fibers (Kidokoro and Saito, 1988) as well as acetylcholine receptor distribution during synaptogenesis (Kummer et al, 2006). Furthermore, synaptic activity plays a crucial role in the transition from multiple innervation to single innervation at developing neuromuscular synapses (Wyatt and Balice-Gordon, 2003). In addition to the global effects exerted by suprathreshold spontaneous synaptic activities, recent studies suggest that spontaneous miniature synaptic transmission, independent of evoked transmitter release, may regulate local postsynaptic protein synthesis and stabilize the structure and function of developing synapses (McKinney et al, 1999;Saitoe et al, 2001;Chung and Kavalali, 2006;Sutton et al, 2006).…”
Section: The Possible Role Of Enhanced Spontaneous Neurotransmission mentioning
confidence: 99%